Comportamiento productivo de cerdos landrace en la etapa de crecimiento, suplementados con harina de moringa. - Valverde Naranjo, Anderson Joel (2020)
In the present investigation the productive behavior of Landrace pigs is evaluated in the growth stage, supplemented with Moringa flour, the objectives were; Determine the best food ration in 200g / animal / day, 300g / animal / day and 400g / animal / day for Landrace pigs; Determine the effect of rations with Moringa flour on weight gain and feed conversion of pigs in the growth stage; Perform the economic analysis in the cost / benefit ratio; Determine the reaction of Moringa in the body of pigs according to the dose. For this investigation, select a completely randomized block design (DBCA) with 4 treatments and 4 repetitions, with a total of 16 experimental units, the experimental results showed that for the most part, the variables obtained a statistical significance (*); The best food ration according to weight gain, and morphological characteristics, 400 mg / animal, obtaining a GPT of 32 Kg, obtaining an average CA of 2.03, presenting the best cost-benefit ratio between treatments with an index of 1 , 61, in addition to this determines that the addition of Moringa flour did not cause any alteration at the physiological, renal or hepatic level.